Integrated assessment framework as a tool for identifying the type of state aid - Bartosz Bartniczak (Economic and Environmental Studies (E&ES), 2013)
Implementing the concept of sustainable development is one of the major challenges facing the modern world. One of the instruments creating sustainable development might be state aid. State aid has an impact not only on the economic sphere but also the environmental and social sphere. State aid can have beneficial, harmful or neutral impact on the implementation of sustainable development. In reality, the design of aid programs does not assess its impact on sustainable development. Judgments are only a measure of the impact on competition, which does not necessarily support sustainable development. The main objective of the article is to present an integrated assessment framework as a tool for identifying beneficial state aid from the point of view of sustainable development. The characteristics of this tool will be presented. Furthermore, a practical tool for assessing the state aid granted in Poland on the basis of selected assistance programs will be discussed, and the directions of change needed for improving this tool to improve the assessment of impact of the granted aid will be elaborated.
Keywords: 330; state aid; sustainable development; harmful state aid; neutral state aid; beneficial state aid